2005
DOI: 10.1158/1078-0432.ccr-04-2188
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Treatment with Tetra-O-Methyl Nordihydroguaiaretic Acid Suppresses the Growth of Human Xenograft Tumors

Abstract: Purpose: We have previously shown that the transcriptional inhibitor tetra-O-methyl nordihydroguaiaretic acid (M 4 N) induces growth arrest in tumor cells and exhibits tumoricidal activity when injected intratumorally into tumor cell explants in mice. The experiments reported here were designed to determine whether M 4 N can be given systemically and inhibit the growth of five different human xenograft tumors. Experimental Design: Nude (nu/nu) mice bearing xenografts of each of five human tumor types (i.e., he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 29 publications
3
48
1
Order By: Relevance
“…One of those that directly affect survivin expression, tetra-O-methyl nordihydroguaiaretic acid (M(4)N), was shown to suppress Sp1-dependent survivin gene transcription and activate the mitochondrial apoptotic pathway in transformed cells (109). Moreover, M(4)N suppressed the growth of human xenograft tumors following systemic treatment (110). However, considering that the compound is a global transcription inhibitor, both survivin-dependent and survivin-independent pathways are thought to be responsible for drug-induced cell death in tumors (111).…”
Section: Hsp90 Inhibitorsmentioning
confidence: 99%
“…One of those that directly affect survivin expression, tetra-O-methyl nordihydroguaiaretic acid (M(4)N), was shown to suppress Sp1-dependent survivin gene transcription and activate the mitochondrial apoptotic pathway in transformed cells (109). Moreover, M(4)N suppressed the growth of human xenograft tumors following systemic treatment (110). However, considering that the compound is a global transcription inhibitor, both survivin-dependent and survivin-independent pathways are thought to be responsible for drug-induced cell death in tumors (111).…”
Section: Hsp90 Inhibitorsmentioning
confidence: 99%
“…One of the derivatives, tetra-Omethyl nordihydroguaiaretic acid (M4N) was shown to be able to induce G2 cell cycle arrest and exhibit anti-tumor activities in vivo [33,34]. The compound is currently in clinical trials in solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The compound is currently in clinical trials in solid tumors. Mechanistic studies demonstrated that M4N induced cell cycle block and its anti-tumor activity was mediated by inhibiting expression of Sp1-dependent Cdc2 and survivin genes [34,35]. Recently, hedamycin was identified to inhibit and DEC1 to upregulate survivin transcription using the same mechanisms [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…In our experiments, NDGA and M 4 N showed similar antiviral activities against WNV and ZIKV at concentrations near to those that can be detected in tissues and plasma of treated animals (39,40). However, our CC 50 values for each compound evidenced that M 4 N displayed a reduced toxicity in comparison to that of NDGA.…”
Section: Discussionmentioning
confidence: 43%